The patients' library movement: an overview of early efforts in the United States to establish organized libraries for hospital patients. - Panella, N M (1996)
The patients' library movement in the United States, a dynamic, cohesive drive begun and sustained by librarians and physicians, strove to promote placement of organized libraries for patients in hospitals. It took shape in the early years of this century, evolving from its proponents' deeply held conviction that books and reading foster the rehabilitation of sick people. The American Library Association's World War I service to hospitalized military personnel dramatically reinforced the conviction; the post-World War I institution of public library extension services to general hospitals explicitly reflected it. Enormous energy was infused into the patients' library movement. Throughout the first half of this century, there were sustained efforts not only to establish organized libraries for hospitalized people but also to expand and systematically study bibliotherapy and to shape patients' librarianship as a professional specialty. The movement's achievements include the establishment of patients' library committees within national and international associations; impetus for development of academic programs to train patients' librarians; and publication, from 1944 through 1970, of successive sets of standards for hospital patients' libraries. The first of these remain the first standards written and issued by a professional library association for a hospital library.